Foreign Direct Investment, Macroeconomic Stability and Technological Advancement in Nigeria’s Economic Development - Bosede, Adegboye Folasade; Motunrayo, Gbebikan Anthonia (Mahesa Research Center, 2025)
This research investigated the impact of foreign direct investment (FDI), macroeconomic variables specifically inflation and exchange rate, and technological advancement especially financial technology (fintech) products of mobile banking transactions and point-of-sale on Nigeria’s economic development. Given the revolutionary potential of technology in the modern global economy, the study investigates how stable macroeconomic variables can draw foreign direct investment (FDI) to Nigeria's tech-driven industries, including digital finance, health technology, and telecommunications. This research utilized secondary data from 1990 till 2023 obtained from the Central Bank of Nigeria, and adopted the multiple regression analysis to estimate the variables. The findings showed that FDI, inflation, exchange rate, mobile banking transaction, and point-of-sale usage significantly impact GDP per capita. This research emphasizes that foreign investment may boost innovation, increase productivity, and promote sustainable growth when it is properly focused on technological sectors. Policy recommendations include fostering a stable economic environment, investing in digital infrastructure, and designing incentives for foreign investors targeting high-tech industries. This aligns with national development goals and contributes to Africa’s broader digital transformation agenda.